REFORMULATION OF CONSUMER PROTECTION LEGAL POLICIES IN THE DIGITAL BUSINESS ERA IN INDONESIA - Muchammad Shidqon Prabowo; Dewi Sulistianingsih (Diponegoro Law Review, 2023)
This study discusses the Reformulation of Consumer Protection Legal Policies in the Digital Business Era in Indonesia. The purpose of this study is to understand and analyze the reformulation of consumer protection legal policies in the digital business era in Indonesia. The research method used is descriptive analytical method, normative juridical problem approach, primary and secondary legal materials. Descriptive data analysis qualitative deductive thinking. The result of the study is the current condition of consumer protection in Indonesia is measured through Law Number 8 of 1999 which regulates the behavior of business actors with the ultimate goal of providing protection to consumers. However, there are things that are considered so that this UUPK can be reformulated with the aim of perfecting the law. Consumers need to get protection not only from producers but also from the market place. These rules must be clear and firm so that consumers are truly protected.